Individual Burden of Psoriasis (I-BOP): Building and Validation of a New Scoring Tool for Patients with Psoriasis - Ezzedine K; Fougerousse AC; Aubert R; Monfort JB; Reguiaï Z; Shourick J; Taieb C; Maccari F (Dove Medical Press, 2020)
Khaled Ezzedine, 1 Anne Claire Fougerousse, 2, 3 Roberte Aubert, 4 Jean-Benoît Monfort, 5 Ziad Reguiaï, 3, 6 Jason Shourick, 7 Charles Taieb, 8, 9,* François Maccari 3, 10,* 1Private Pratice, La Varenne Saint Hilaire, France; 2Hôpital d’instruction des armées, Saint-Mandé, France; 3Resopso, Paris, France; 4France Psoriasis, Association de Patients, Paris, France; 5Hôpital Cochin, Paris, France; 6Service de Dermatologie, Polyclinique Courlancy-Bezannes, Reims, France; 7Université Paris Sud, Paris, France; 8Santé Publique, Hôpital Necker Enfants Malades, Paris, France; 9European Market Maintenance Assessment, Fontenay-sous-Bois, France; 10EA EpiDermE UPEC-Université Paris-Est Créteil, Creteil, France*These authors contributed equally to this workCorrespondence: Charles Taieb Tel +33 771 772 100Email charles.taieb@emma.clinicBackground: Psoriasis impacts independently of its severity on patients’ lifestyle and quality of life (QoL).Aim: To build a tool for assessing the patient-reported psoriasis burden.Methods: An expert group created a questionnaire using a standardized methodology building questionnaires assessing quality of life issues. The questionnaire was translated from French into a cultural and linguistically validated US English version.Results: A conceptual questionnaire of 54 questions was created. The confirmatory analyses resulted in a 10-feature questionnaire divided into 4 internally consistent domains with a Cronbach’s alpha coefficient of 0.9. It was reproducible and highly reliable. It correlated well with the Dermatology Life Quality Index (DLQI), Perceived Stress Scale (PSS), and SF-12 mental and SF12 physical scores.Conclusion: This tool allows for the first time to assess the burden of psoriasis patients. Its use may allow improving medical and nonmedical patient care, thus improving their daily life.Keywords: disease burden, psoriasis, quality of life, questionnaire, standardized method